The formation of the ‘I’ through the ‘Eye’ in Derek Walcott’s Poetry - Raza, Amra (Journal of Research in Humanities, 2023)
On a closer analysis of Derek Walcott‟s poems (1948-84), it gradually becomes evident that the poet’s gaze in recreating space also initiates a complex process of identification. This paper seeks to examine how Walcott self consciously uses shiny, transparent and opaque surfaces to generate a series of images of the Self in various contexts of the past and present. The „eye‟ thus becomes an instrument for the formation of the “I". In the course of this study I will draw upon Jacques Lacan’s psychoanalytic theory of the Gaze and in particular upon the Mirror Stage of Identification. Lacan’s theory restricts itself mainly to man-made mirrors.